Durability properties of novel coating material produced by alkali-activated/cement powder. (11th January 2023) - Phiangphimai, Chattarika; Joinok, Gonganok; Phoo-ngernkham, Tanakorn; Damrongwiriyanupap, Nattapong; Hanjitsuwan, Sakonwan; Suksiripattanapong, Cherdsak; Sukontasukkul, Piti; Chindaprasirt, Prinya
Highlights: AACP paste showed a potential coating material for improving the durability of RC structures. AACP paste exhibited superior durability to PC paste. HCP values of AACP paste-treated-DB were lower than those of no-treated and PC paste-treated-DB. AACP paste produced by just adding water could be used as alternative coating material. Abstract: This paper presents a feasibility study on the use of alkali-activated/cement powder (AACP) paste as a potential coating material for improving the durability of structures and protecting buildings exposed to marine environments. The AACP was synthesized by geopolymer powder (GP), Portland cement (PC), and silica fume (SF). The water-to-binder ratio of 0.45 and sodium hydroxide solution of 2 M were used to activate the reaction products of the AACP paste. The experimental tests consisted of the retained compressive strength and weight change after exposure to 5 % sulfuric acid (H2 SO4 ) solution, 5 % magnesium sulfate (MgSO4 ) solution, and tap water (H2 O), and chloride migration coefficient (RCM). The corrosion probability of concrete reinforcement with surface treatment of deformed bar (DB) using the half-cell potential (HCP) test was also evaluated. Test results showed that the AACP paste exhibited superior durability to PC paste, as evidenced by its relatively low strength loss and weight change. In addition, the chloride diffusion coefficient of AACP pastes was 32.7 to 77.6 times lower than that of PC paste. For the corrosion probability of concrete reinforcement, the average HCP values of the AACP paste-treated-deformed bar were lower than those of the no-treated or PC paste-treated-deformed bar, especially for the AACP paste prepared by GP without PC.